Comparative study of dental cephalometric patterns of Japanese-Brazilian, Caucasian and Mongoloid patients - Renata Sathler; Arnaldo Pinzan; Thais Maria Freire Fernandes; Renato Rodrigues de Almeida; José Fernando Castanha Henriques (Dental Press Editora, 2014)
INTRODUCTION: The objective of this study was to identify the patterns of dental variables of adolescent Japanese-Brazilian descents with normal occlusion, and also to compare them with a similar Caucasian and Mongoloid sample. METHODS: Lateral cephalometric radiographs were used to compare the groups: Caucasian (n = 40), Japanese-Brazilian (n = 32) and Mongoloid (n = 33). The statistical tests used were one-way ANOVA and ANCOVA. The cephalometric measurements used followed the analyses of Steiner, Tweed and McNamara Jr. RESULTS: Statistical differences (P < 0.05) indicated a smaller interincisal angle and overbite for the Japanese-Brazilian sample, when compared to the Caucasian sample, although with similar values to the Mongoloid group. CONCLUSION: The dental patterns found for the Japanese-Brazilian descents were, in general, more similar to those of the Mongoloid sample.